Utility of pediatric early warning score at emergency room in predicting the level of care required for next 48 h: A single-center, prospective, observational study - Anas Parwaiz; Nitika Agrawal; Alpa Gupta; Ashish Simalti; Manju Kedarnath (Wolters Kluwer Medknow Publications, 2024)
Background: Pediatric scores such as the Pediatric Early Warning Score (PEWS) are based on parameters available at the bedside. The aim of this study was to assess the utility of PEWS to determine the need for critical care support within the next 24-48 h. this study aimed to see if PEWS could predict a suitable level of care, namely ward, high-dependency unit (HDU), or pediatric intensive care unit (PICU). Subjects and Methods: It was a prospective observational study and a convenient sample method was used with children of age groups from 1 month to 18 years, coming to the pediatrics department being the subject. We correlated the level of care at admission and also after 48 h with PEWS at the time of admission of children already intubated, children on inotropes at the time of admission, children with surgical illness, and children admitted only for procedure/procedural sedation were excluded from this study. The Brighton PEWS was used to calculate PEWS. Results: A total of 953 patients were enrolled in this study. In this study, the likelihood of admission to PICU correlated well with PEWS above 6 with a positive predictive value of 56% and a negative predictive value of 99.43%. Conclusions: The admission PEWS can be used as an effective tool for deciding the level of care area. Score <3 admission PEWS can be kept at the ward, while >3 score at HDU/PICU where frequent periodic monitoring should be done.